Looking down the microscope at the big picture – Interview with Michelle Casanova - Casanova, M.; McDonald, Tein (Wiley-Blackwell Publishing Ltd, 2018)
© 2018 Ecological Society of Australia and John Wiley & Sons Australia, Ltd Michelle Casanova is a widely published researcher specialising in the taxonomy of Australia's freshwater algae – as well as a rural landholder who understands the need for farmers to utilise the landscape. Michelle combines her work as a researcher with increasing involvement in management and policy through her region's Catchment Management Board and Victoria's Scientific Advisory Committee.